A kis- és középvállalkozások finanszírozásának aktuális kérdései az Európai Unióban - Czagány, László (Közép-Európai Közlemények, 2010)
The European Council passed during its may 2006 meeting the Small Business Act, which contain the initiatives to facilitate sustainable growth and enhanced competitiveness for european small- and middle-sized enterprises. The first part of the paper discusses the general problems of small business financing in accordance with this document, then individually assesses the situation in eight countries.